ChemInform Abstract: Potassium, Cesium, and Ammonium Peroxogermanates with Inorganic Hexanuclear Peroxo Bridged Germanium Anion Isolated from Aqueous Solution. Issue 42 (October 2015) - Medvedev, Alexander G.; Mikhaylov, Alexey A.; Churakov, Andrei V.; Vener, Mikhail V.; Tripol'skaya, Tatiana A.; Cohen, Shmuel; Lev, Ovadia; Prikhodchenko, Petr V.
Abstract K6 [Ge6(μ‐O2)6(μ‐O)6 (OH)6]·14H2O (I), Cs4.2(NH4)1.8 [Ge6(μ‐O2)6(μ‐O)6 (OH)6]·8H2O (II), and K2.4(NH4)3.6 [Ge6(μ‐O2)6(μ‐O)6 (OH)6]·6H2O (III) are isolated from K or Cs hydroxogermanate solutions by addition of aq.